The national plan of development 2018-2022: “Pact for Colombia, pact for equity” - Vallejo Zamudio, Luis E. (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The President of the Republic, Iván Duque Márquez, sanctioned the development plan “Pact for Colombia, pact for equity”, established by means of Law 1955 of May 25, 2019. This plan, which will be executed in the four-year period 2018–2022, becomes the road map of public policy and investments during his presidential term.